Change of electoral geography in England and Wales through Brexit referendum - Yu, Songlin (The University of Edinburgh, 2018)
The aim of this research is using statistical and GIS software to understand the electoral geography change through Brexit referendum in England and Wales. This research especially focuses on verifying the spatial autocorrelation and spatial heterogeneity phenomenon. Understanding the supporter composition of the UKIP, and how they changed their decision in 2017 is also a theme of this project. The results support that the result of the 2017 general election is not only reflected in the Brexit referendum result, but both the Brexit referendum and 2017 general election result reflected a long-term political divide in England and Wales. Labour continued its supporter composition change trend through Brexit referendum – more social liberal and metropolitan. However, Conservatives experienced an electoral geography change through the Brexit referendum. Meanwhile, there is insufficient evidence to support that the UKIP is a party which is supported by 'left-behind' people. In Thames Estuary, UKIP may have obtained support from both former two major parties’ supporter base.
The change of electoral geography in England and Wales through Brexit referendum
Keywords: Electoral Geography; MSc Geographical Information Science; GIS; Brexit; England and Wales; Cluster and outlier analysis; Spatial autocorrelation; GWR model; Spatial heterogeneity